Seismic hazard analysis using Deterministic Seismic Hazard Analysis (DSHA) Method: A case study in Southern Malang District, East Java - Widodo Eko Prasetyo; Listyo Yudha Irawan; Rudi Hartono; Endratno Budi Santosa (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2023)
Indonesia is a country that has a high earthquake threat. The United States Geological Survey (USGS) recorded that Indonesia experienced 5,439 earthquakes with a magnitude of Mw 5. Geologically, Indonesia is located about 200 km from the subduction zone of the Indo-Australian and Eurasian plates. Malang Regency faces the subduction of the Indo-Australian and Eurasian plates. Earthquakes that occur in plate subduction areas will propagate in various directions, including to Malang Regency. Thus, Malang Regency, especially in the southern part, has a high earthquake threat. This study aims to calculate the earthquake threat using a deterministic approach. Earthquake threats can be calculated using the Deterministic Seismic Hazard Analysis (DSHA) method. This study obtained the Mc. Guirre and Donovan attenuation function. These two attenuation functions produce different Peak Ground Acceleration values. The calculations with the Mc. Guirre attenuation function has a range of PGA values from 38,76461 gals to 69,78215 gals. Meanwhile, the Donovan attenuation function calculation produces a range of PGA values from 41.97550 gals to 76.21376 gals. Based on the value of ground acceleration during an earthquake, Bantur, Gedangan, and Sumbermanjing sub-districts are the sub-districts with the highest earthquake threat level in Southern Malang Regency. Tirtoyudo Village, Tirtoyudo District, Malang District has a lower PGA value when compared to Gedangan District. However, the amount of damage to buildings in this subdistrict was much higher. Since the building structure in Tirtoyudo Village cannot withstand ground shaking due to the earthquake, there is damage to the structure of the building.